Optimization of the Treatment of Chronic Generalized Periodontitis in Postmenopausal Women - Bustanovna, Islamova Nilufar; Rustamovich, Bekmurodov Luqmon; ugli, Asatboyev Jaloliddin Asliddin (American Journal of Biomedicine and Pharmacy, 2026)
Chronic generalized periodontitis is a multifactorial inflammatory disease that significantly affects postmenopausal women due to estrogen deficiency, increased bone turnover, and alterations in immune response. These physiological changes exacerbate periodontal tissue destruction, alveolar bone loss, and compromise treatment outcomes. This study aims to evaluate and optimize therapeutic approaches for postmenopausal women with chronic generalized periodontitis by integrating conventional nonsurgical therapy, adjunctive local and systemic antimicrobial agents, host-modulation strategies, and regenerative periodontal procedures. Sixty postmenopausal women with moderate to severe chronic generalized periodontitis were recruited and followed for 12 months. Clinical parameters assessed included probing depth, clinical attachment level, bleeding on probing, plaque index, and gingival index. Radiographic evaluation was conducted using periapical radiographs and cone-beam computed tomography to monitor alveolar bone height and density. Biochemical analysis of gingival crevicular fluid quantified inflammatory cytokines including IL-1β, TNF-α, and MMP-8. Patient-centered outcomes including pain, comfort, mastication efficiency, and oral health-related quality of life were evaluated using OHIP-14 and visual analog scales. Results demonstrated that integrating scaling and root planing with local antimicrobial therapy and systemic host-modulation treatment significantly improved clinical parameters, reduced inflammatory markers, and stabilized alveolar bone compared with conventional therapy alone. Regenerative interventions such as guided tissue regeneration and enamel matrix derivative application provided further benefit in sites with localized severe bone defects. These findings emphasize that optimization of periodontal therapy in postmenopausal women requires individualized, multifactorial strategies targeting both local periodontal factors and systemic influences, combined with strict maintenance protocols and patient adherence for sustained long-term outcomes.